Proceedings of the Second International Conference on the Reclamation, Treatment, and Utilization of Coal Mining Wastes, Nottingham, England, September 7-11, 1987 - Rainbow, A. K. M., 1936- (Advances in mining science and technology, 1987)
Destined to become a major reference work, this book presents a wide range of specialist papers on the exploitation of coal mining wastes (minestone). Up-to-date developments and research results are reported from all over the world, providing a wealth of information for civil and mining engineers, environmentalists, and land reclamation specialists.